2015
DOI: 10.2217/fon.15.97
|View full text |Cite
|
Sign up to set email alerts
|

KRAS exon 2 mutations influence activity of regorafenib in an SW48-based disease model of colorectal cancer

Abstract: In SW48 cells, exon 2 mutations of the KRAS gene may influence antitumor effects of regorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…This observation supports the hypothesis that KRAS exon 2 mutation variants are associated with a differing spectrum of clinical outcome [4, 8, 27]. It might be speculated that the reason for differing outcomes could be mediated by differing activation of KRAS -depending pathways by distinct mutation variants, as suggested previously with high baseline activation and potentially aggressive biology in G12C variants [28]. In addition, the poor outcome of patients with G12C mutant mCRC might be of clinical relevance as allele-specific inhibitors may provide therapeutic options in the future [29, 30].…”
Section: Discussionsupporting
confidence: 87%
“…This observation supports the hypothesis that KRAS exon 2 mutation variants are associated with a differing spectrum of clinical outcome [4, 8, 27]. It might be speculated that the reason for differing outcomes could be mediated by differing activation of KRAS -depending pathways by distinct mutation variants, as suggested previously with high baseline activation and potentially aggressive biology in G12C variants [28]. In addition, the poor outcome of patients with G12C mutant mCRC might be of clinical relevance as allele-specific inhibitors may provide therapeutic options in the future [29, 30].…”
Section: Discussionsupporting
confidence: 87%
“…The reason for the distinction of prognosis is still not well understood. Different biological behaviors of individual mutation variants, such as differential activation of the KRAS downstream effect pathways, have been suggested [ 30 ]. However, conflicting views have been proposed, and more frequent KRAS variants, such as G12D and G12V, were reported to lack obvious impacts on OS in univariate and multivariate Cox analyses [ 29 ].…”
Section: Kras Mutations and Their Roles In Crcmentioning
confidence: 99%
“…In the case of unresectable mCRC, Modest et al, among others, demonstrated that KRAS exon two mutation variants were associated with heterogeneous outcomes for both OS and PFS. A possible explanation may involve differing activation of KRAS‐dependent pathways by distinct mutational variants . The author's group was the first to assess whether different codon‐ or point‐specific KRAS exon two mutations have variable prognosis in a surgical cohort of CRLM .…”
Section: Resultsmentioning
confidence: 99%
“…37 However, it is important to recognize that the exact combination of KRAS mutation and clinicopathologic factors differed across these three studies, which in combination with the lack of external validation, limits their generalizability and practical use beyond the cohorts in which they were derived. 20,38,39 The authorʼs group was the first to assess whether different codon-or pointspecific KRAS exon two mutations have variable prognosis in a surgical cohort of CRLM. 40 Consistent with the studies in unresectable patients, we found that specific KRAS point mutations were associated with poor survival, while other point mutations had a similar survival as wild-type tumors.…”
Section: Kras Alone Vs Genetic Risk Score Systems For Surgical Selementioning
confidence: 99%